Comparative Transcriptome Analysis Reveals Heat-Responsive Genes in Chinese Cabbage (Brassica rapa ssp. chinensis) - Wang, Aihua; Hu, Jihong; Huang, Xingxue; Li, Xia; Zhou, Guolin; Yan, Zhixiang (Frontiers in Plant Science, 2016)
Abstract Chinese cabbage (B. rapa ssp. chinensis) is an economically and agriculturally significant vegetable crop and is cultivated extensively in the world. Heat stress disturbs cellular homeostasis and causes a visible growth inhibition of shoot and root, severe retardation in growth and development, and even death. However, few studies on the trancriptome profiling of heat stress in non-heading Chinese cabbage. In this study, we investigated the trancript profiles of non-heading Chinese cabbage from heat-sensitive and -tolerant varieties ‘GHA’ and ‘XK’ in response to high temperature using RNA sequencing (RNA seq). Approximately 760 genes were differentially expressed between the two varieties ‘GHA’ and ‘XK’. The responsive genes can divide into three categories with the time of heat treatment increasing: response to stimulus, programmed cell death and ribosome biogenesis. Differentially expressed genes (DEGs) were identified in the two varieties, including transcription factors (TFs), kinases/phosphatases, genes related to photosynthesis and effectors of homeostasis. Many TFs involved in heat response of Chinese cabbage, inculding NAC069 TF was up-regulated at all the heat treatment stages. And their expression levels were also validated by quantitative real-time-PCR (qRT-PCR). These candidate genes will provide genetic resources for further improving the heat-tolerant characters in non-heading Chinese cabbage.